A superação do solipsismo em Sartre - Reyes, Raimundo de María Mena (2007)
The present dissertation has the intention to establish how measured Sartre obtains to surpass the solipsism of the conscience, interpreting the registers that compose the phenomenological concept of Looking at, in The Being and the Nothing. After to define the concept of solipsism, will be in evidence the problem that it implies and that, according to Sartre, is originated from the notion of Cartesian Cogito. It is manifested the construction of conceptual-description of the notion of Looking at and the paper that this concept plays in the measure that offers a not cognitive evidence of the Other s existence. There are evaluated the contributions and obstacles of the concept s use of Looking at in the Sartrean attempt of overcoming the solipsism. Concluding, it is verified the reach of this Cogito extended , as Sartre calls to the experience of Looking at. From a phenomenological point of view, it results evident that the solipsism is a false problem and that the Other exists without no doubt. Ontologically, is more difficult to have this certainty, therefore Sartre does not resign to the starting point of Cogito.